Pengaruh Penggunaan Natrium Tripolyphospate (Na5p3o10) Terhadap Sifat Fisik Beton Cor Bawah Air Berlumpur - Fitri Lestari; Ismeddiyanto Ismeddiyanto; Andre Novan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Concrete that used for underwater construction should be proportioned so that the concrete is capable to consolidate by its self weight and develop the strength. The aim of this research is to purpose the use of natrium tripolyphosphate as an additive to concrete mix that will be used for underwater construction. The amount of natrium tripolyphosphate added to the concrete mix was derived from three trial mix, namely trial mix I, II and III. Based on trial mix I natrium tripolyphosphate can used for underwater construction and the best percentage of filler is 15% by weight of fine aggregate, while based on trial mix II all of concrete had segregation and the concrete with 10% of natrium tripolyphosphate had the least segregation and based on trial mix III natrium tripolyphosphate can diluted the concrete mix and helps harden the mixture. The result showed that the slump flow value for concrete with 10% of natrium tripolyphosphate was 673,3 mm, this value fit the slump value suggested by ASTM-C-161, that slump for SCC should be within the range of 550 mm and 850 mm. The mud rates obtained from the test result using centrifuge and measurement were 28,62% and 26,87%. The values for porosity and permeability in normal water at 28 days are 21,97% and 1,04x10-9 m/s, and while the values for porosity and permeability in muddy water at 28 days are 23,27% and 1,61x10-9 m/s.Keywords: Underwater concrete, natrium tripolyphospate, muddy water, physical properties